Collective Bargaining for Women: How Unions Can Create Female-Friendly Jobs - Viola Corradini; Lorenzo Lagos; Garima Sharma (Institute of Labor Economics (IZA), 2022)
Why aren't workplaces better designed for women? We show that changing the priorities of those who set workplace policies can create female-friendly jobs. Starting in 2015, Brazil's largest trade union federation made women central to its bargaining agenda. Neither establishments nor workers choose their union, permitting a difference-in-differences design to study causal effects. We find that "bargaining for women" increases female-centric amenities in collective bargaining agreements, which are then reflected in practice (e.g., more female managers, longer maternity leaves, longer job protection). These changes cause women to queue for jobs at treated establishments and separate from them less—both revealed preference measures of firm value. We find no evidence that these gains come at the expense of employment, workers' wages, or firm profits. Hence, prioritizing women's preferences in decision-making can lower within-firm gender inequality through more efficient bargaining.
Keywords: J31; J33; J51; J52; 330; gender disparities; amenities; collective bargaining; unions